The influence of dynamic capabilities on organizational resilience: a study on Malaysian food and beverage micro, small and medium enterprises with business innovation as a mediator and entrepreneurial orientation as a moderator - Abdul Rahman, Syahrul Nadwani (2024)
Modern enterprises must be robust. Micro, small, and medium enterprises (MSMEs) are vulnerable to external forces. The business is easy to initiate, but entrepreneurs struggle to maintain it. The concept of organizational resilience is something that MSME owners need to become familiar with to understand what they need to do to be resilient. This is because the demand for agility and robustness is growing. This research is mostly about food and beverage (F&B) service activities that offer full meals or drinks that are ready to eat or drink right away. The objective of this study is to conduct a more in-depth examination of the substantial effect of dynamic capabilities on Malaysian MSMEs. Additionally, it aims to explore the function of business innovation as a mediator and entrepreneurial orientation as a moderator. Teece's Dynamic Capabilities provides the foundational theory around which the study's framework was built. Considering the quantitative methodology employed, a comprehensive review of the literature was undertaken to develop the questionnaires. With a response rate of 72.01 percent, the survey questionnaires were distributed at random to 768 business owners, administrators, and/or members of the management team of F&B service operations in Northern Malaysia, constituting the sample. The gathered data were analysed using the PLS-SEM approach version 4. The findings demonstrate that the presence of dynamic capabilities and business innovation has a positive effect on organizational resilience. This highlights the significance of these factors for MSMEs and suggests that they should be given careful attention. Furthermore, the study found that business innovation mediates the relationship between dynamic capabilities and organizational resilience. However, it was observed that entrepreneurial orientation had a substantial and adverse effect on the relationship between dynamic capabilities and business innovation, exerting a moderating influence. Apparently, the study shows prevailing contribution in the demographic composition of Malaysian F&B MSMEs, which is heavily influenced by settings, particularly the prevalence of Gen X and Millennials. In addition, this study provides empirical evidence for Dynamic Capabilities Theory (DCT) by showing that resilient businesses, particularly those with fewer resources, rely heavily on dynamic capabilities. Likewise, the practical contributions give insights regarding how policymakers and industry performers in Malaysia may implement programs and policies that promote MSMEs in achieving more creative, entrepreneurial, and resilient. Lastly, the study also includes a discussion of its limitations and suggestions for future research.